A Preliminary Simulation Study of Dose-Guided Adaptive Radiotherapy Based on Halcyon MV Cone-Beam CT Images With Retrospective Data From a Phase II Clinical Trial - Huang, Yuliang; Wang, Haiyang; Li, Chenguang; Hu, Qiaoqiao; Liu, Hongjia; Deng, Jun; Li, Weibo; Wang, Ruoxi; Wu, Hao; Zhang, Yibao (Frontiers in Oncology, 2020)
Background and purpose: To evaluate the feasibility of dose-guided adaptive radiotherapy (ART) based on deformable image registration (DIR) using fractional MVCBCT images from Halcyon system that uses identical beams for treatment and imaging, and to retrospectively investigate the influence of anatomic changes on target coverage and organ-at-risk (OAR) sparing across various tumor sites. Materials and methods: Four hundred and twenty-two MVCBCT images from 16 patients (3 head and neck, 7 thoracic, 3 abdominal and 3 pelvic cases) treated in a phase II clinical trial for Halcyon were selected. DIR between the planning CT and daily MVCBCT image was implemented by Velocity software to create pseudo CT. To investigate the accuracy of dose calculation on pseudo CT, three evaluation patients with rescanned CT and adaptive plans were selected. Dose distribution of adaptive plans calculated on pseudo CT was compared with that calculated on the rescanned planning CT on the three evaluation patients. To investigate the impact of inter-fractional anatomic changes on target dose coverage and dose to OARs of 16 patients, fractional dose was calculated and accumulated incrementally based on deformable registration between planning CT and daily MVCBCT images. Results: Passing rates using 3mm/3%/10% threshold local gamma analysis were 93.04%, 96.00% and 91.68% respectively for the 3 evaluation patients between the reconstructed dose on pseudo CT (MVCBCT) and rescanned CT, where accumulated dose deviations of over 97% voxels were smaller than 0.5Gy. PTV D95% and D90% of the accumulated dose could be as low as 93.8% and 94.5% of the planned dose respectively. OAR overdose of various degrees were observed in the 16 patients relative to the planned dose. In most cases, OARs’ DVH lines of accumulated and planned dose were very close to each other if not overlapping. Among cases with visible deviations, the differences were bilateral without apparent patterns specific to tumor sites or organs. Conclusion: As a confidence building measure, this simulation study suggested the possibility of ART for Halcyon, based on DIR between planning CT and MVCBCT. Preliminary clinical data suggested the benefit of patient-specific dose reconstruction and ART to avoid unacceptable target under-dosage and OAR over-dosage